2022
DOI: 10.1038/s41598-022-13003-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of post-activation performance enhancement and different warm-up protocols on swim start performance

Abstract: This study aimed to examine the effects of post-activation performance enhancement (PAPE) on swim start performance and lower body power performance after different warm-up protocols. Ten male national-level swimmers performed three different warm-ups: (i) a swim-specific warm-up (SW, control protocol); (ii) PAPE (an experimental protocol); and (iii) SW followed by PAPE (SW + PAPE, an experimental protocol). PAPE consisted of performing three series of 5 drop jumps. A repeated-measures ANOVA showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
(83 reference statements)
1
9
0
Order By: Relevance
“…The results of this study [86] showed improvements in mean and peak vertical forces, which resulted in an improvement of the resultant take-off velocity which may be due to a greater stimulation in the front leg by the eccentric overload [33]. Two recent studies obtained similar results but without using sophisticated equipment [40,87]. In the study of Waddingham et al [40], a 400-m varied pace in-water warm-up that included 2 × 15-m maximal swim starts, was compared to the same warm-up followed by: i) 3 × 3 resistance bands squat protocol (loads between 27.2 -68 kg; ii) 3 × 3 weighted jump squats (15% bodyweight), and; iii) 2 × 5 drop jumps from a box [40].…”
Section: Effects On the Swimming Start Performancesupporting
confidence: 57%
“…The results of this study [86] showed improvements in mean and peak vertical forces, which resulted in an improvement of the resultant take-off velocity which may be due to a greater stimulation in the front leg by the eccentric overload [33]. Two recent studies obtained similar results but without using sophisticated equipment [40,87]. In the study of Waddingham et al [40], a 400-m varied pace in-water warm-up that included 2 × 15-m maximal swim starts, was compared to the same warm-up followed by: i) 3 × 3 resistance bands squat protocol (loads between 27.2 -68 kg; ii) 3 × 3 weighted jump squats (15% bodyweight), and; iii) 2 × 5 drop jumps from a box [40].…”
Section: Effects On the Swimming Start Performancesupporting
confidence: 57%
“…The present study confirmed this most-desired effects since knee flexion torque was significantly increased after the warm-up. Such result is often obtained in the literature with various conditioning exercises on single joint or whole-body outcomes [ 1 , 46 , 47 ]. In contrast, our results indicated maximal torque returned to baseline after stretching whatever the modality applied (static or neurodynamic nerve gliding technique).…”
Section: Discussionmentioning
confidence: 95%
“…PAPE could have significance in sports competitions and training ( Boullosa, 2021 ; Villalon-Gasch et al, 2022 ; Đurović et al, 2022 ), although there is still much to discover. Many factors can influence the PAPE effect, various protocols can be utilized ( Seitz and Haff, 2016 ; Dobbs et al, 2019 ), and greater difficulty can be added to increase variability and individualize the PAPE response ( Till & Cooke, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is important to use a conditioning activity (CA) with a movement pattern related to the target effort, such as a squat for a jump ( Seitz and Haff, 2016 ; Blazevich & Babault, 2019 ; Boullosa, 2021 ). Many authors have developed effective conditioning protocols based on dynamic and isometric actions, although the latter is rarely used ( Rixon et al, 2007 ; Guerra et al, 2022 ; Pereira et al, 2022 ; Đurović et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%